2016
DOI: 10.1002/bio.3147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solvents, solvent mixture and silver nanoparticles on photophysical properties of a ketocyanine dye

Abstract: The effect of solvents of varying polarity and hydrogen bonding ability, solvent mixture and silver nanoparticles on the photophysical properties of a ketocyanine dye, 2,5-di[(E)-1-(4-diethylaminophenyl) methylidine]-1-cyclopentanone (2,5-DEAPMC), is investigated at room temperature. Solvent effect is analyzed using Lippert-Mataga bulk polarity function, Reichardt's microscopic solvent polarity parameter, and Kamlet's and Catalan's multiple linear regression approaches. The spectral properties better follow Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…In the present case, the S-V plot in the steady state shows the concave upward curve in all ACN + DXN solvent mixtures . The presence of static quenching may be the reason for the presence of static quenching.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In the present case, the S-V plot in the steady state shows the concave upward curve in all ACN + DXN solvent mixtures . The presence of static quenching may be the reason for the presence of static quenching.…”
Section: Resultsmentioning
confidence: 91%
“…In the present case, the S-V plot in the steady state shows the concave upward curve in all ACN + DXN solvent mixtures. 36 The presence of static quenching may be the reason for the presence of static quenching. By comparing Figures 5 and 6 , we can say that both types of quenching, static and dynamic quenching, are present.…”
Section: Resultsmentioning
confidence: 99%
“…Some ketocyanine dyes have been used as laser dyes or photosensitizers and have also found several industrial applications . Recently, we have investigated the influence of silver NPs on the absorption and fluorescence characteristics of two ketocyanine dyes 2,5‐di[(E)‐1‐(4‐dimethylaminophenyl) methylidine]‐1‐cyclopentanone (2,5‐DMAPMC) and 2,5‐di[(E)‐1‐(4‐diethylaminophenyl) methylidine]‐1‐cyclopentanone (2,5‐DEAPMC) . It has been found that spectral properties of these two dyes are sensitive to silver NPs.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Recently, we have investigated the influence of silver NPs on the absorption and fluorescence characteristics of two ketocyanine dyes 2,5-di[(E)-1-(4-dimethylaminophenyl) methylidine]-1-cyclopentanone (2,5-DMAPMC) and 2,5-di[(E)-1-(4diethylaminophenyl) methylidine]-1-cyclopentanone (2,5-DEAPMC). [22,23] It has been found that spectral properties of these two dyes are sensitive to silver NPs. The sensitivity of these dyes to biological systems and the excellent capacity of TiO 2 NPs to carry chemical/biological species in therapeutic applications motivated us to carry out the present investigation.…”
mentioning
confidence: 99%
See 1 more Smart Citation